Evaluasi Kinerja Keuangan Pemerintah Daerah Kota Pare-Pare Sebelum dan Selama Wabah Covid 19 - Yuliana Resca (Syntax Literate, 2023)
The 2018-2020 Budget Realization Report will be used in this study's analysis of the regional government of Pare-Pare Municipality's financial standing. A tool for evaluating financial performance is ratio analysis, which includes measures of decentralization, financial independence, regional financial dependence, effectiveness and efficiency of local revenue, and spending efficiency. This study's statistical analysis followed a descriptive quantitative methodology. According to the study's findings, Pare-Pare City's regional financial independence ratio in 2018–2020 averaged 20.03%, and the degree of decentralization was 16.63%, the ratio of PAD effectiveness for the City Government of Pare-Pare for the 2018-2020 fiscal year was of 96.57%, i.e. <1 or 100, the average PAD efficiency ratio for the Municipal Government of Pare-Pare for the 2018-2020 fiscal year is 20.60%, the average expenditure realized during 2018-2020 is 94.06%. the average spending efficiency ratio of the City Government of Pare-Pare for the 2018 - 2020 fiscal year is 93.10%.